Spacing leadership as an embodied and performative process. (August 2019) - Ropo, Arja; Salovaara, Perttu
Aligned with the recent stream of research on the materiality of organizing, in this article, we develop a conceptualization of leadership as a sociomaterial relationship between human and space. We join the emerging discussions on the 'thing-ness' of leadership and extend these by addressing how an aesthetic, sense-based and embodied knowledge constitutes the sociomateriality of leadership and organizing. With the help of a Lefebvre-inspired framework, we introduce the concept of 'spacing leadership' that explicates leadership as being produced in an embodied and performative process between people and space. To specify this, we thematise three aesthetically embodied categories of knowledge development – senses, feelings and memories – to depict a sociomaterial understanding of leadership and space.